Tourism Management Through Community-Based Ecotourism Development Strategy at Lombang Beach, Sumenep Regency - Pramidita, Jenny; Kurriwati, Nirma; Yulistiyono, Herry (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Community ecotourism is based on references to rural development through the tourism sector which promotes natural resources and supports efforts to preserve the natural environment and increase community participation in management. Thus, generating benefits for the local community's economy. Sumenep Regency, which is located on Madura Island, has a lot of tourism potential. The development strategy carried out uses internal and external factors. The research was conducted in Lombang Village, Batang-Batang District, Sumenep Regency, East Java. This research aims to determine methods that can be used to develop community-based ecotourism on Lombang Beach, Sumenep Regency. The data used uses primary data obtained through interviews used in this research. This research collects data through interviews which are used in the research. Collecting data through a qualitative approach through journals, literature reviews and references. In addition, SWOT analysis at Lombang Beach, Sumenep Regency was used to identify internal and external factors in the ecotourism development plan. The research results show that the strategy for increasing Lombang Beach tourism needs to be developed and attention needs to be paid to it so that it can develop community-based ecotourism on Lombang Beach, Sumenep Regency, to become sustainable and superior tourism. Lombang Beach is still not a sustainable tourist attraction. Therefore, as a local community, being able to develop Lombang Beach tourism into sustainable tourism provides benefits to the community.